Should older patients be offered varicocoele correction to improve their fertility?. (14th March 2014) - Ollandini, G.; Trombetta, C.; Mazzon, G.; de, B.; Bucci, S.; Pavan, N.; Belgrano, E.; Liguori, G.
Summary We reviewed a large number of patients from 2000 to 2010 that underwent varicocoele correction using the retrograde sclerotization approach. Three hundred and seventy‐six of them were included in the study, as they met the inclusion criteria. Mean age at the time of surgery was 32 years (SD: 6.5); 32% of them were 35 years and older. Patients were classified according to the clinical classification (GC) and Sarteschi's Doppler ultrasound classification (GS). The patients showed up at the clinic after an average time of 30 months of referred infertility related (SD: 28.54). Patients underwent pre‐operative assessment with physical examination, sperm analysis and Doppler ultrasound, and again the same assessment at least 3 months after surgery. We evaluated the following parameters: sperm concentration (millions/mL, CONC), percentage motility (a+b, MOT) and the percentage of morphologically typical spermatozoa (MOR). Univariate and Multivariate analysis were performed. The research of Pearson's coefficients was performed to test the correlation between sperm parameters and age, SG, CG. Semen specimens were evaluated according to WHO 1999 criteria. Mean CONC varied from 34.5 to 47.0 millions/mL (+12.5; p < 0.001); MOT from 27.2 to 34.5% (+7.3%; p < 0.001); and MOR from 44.0 to 47.6% (+3.6%; p = 0.001). Univariable and multivariable analysis of variance related to age showed no significant difference of parameters improvement. Pearson's correlation coefficient for pre‐operative and post‐operative sperm MOT related to patients' age was respectively −0.11 (p < 0.001) and −0.18 (p = 0.04). No other significance was found. Usefulness of treating infertile patients affected by varicocoele is confirmed: varicocoele correction leads to significant sperm parameters improvement. There is no evidence of different improvement related to patients' age. The decline in sperm motility related to age of the patients seems to be only age‐dependent: the usefulness of treating patients affected by varicocoele is not influenced by their age: treatment should also be offered to older patients.